Beyond the Call of Duty: Exploring the Motivations, Challenges and Contributions of Aging Volunteers in Military Reserves - Rachel L Saladaga (Randwick International of Education and Linguistics Science Journal, 2023)
Military reservists play a vital role in defense, often balancing their civilian and military responsibilities. This study aimed to investigate the motivations, challenges, and contributions of aging reservists, assessing the impact of their service on personal development and military efficacy. The research sought to identify support factors and strategies for better integration into the military reserves. Utilizing a descriptive qualitative research design, the study collected data through in-depth interviews, providing insights into the motivations and challenges faced by aging reservists. Based on the findings, these individuals are primarily driven by personal satisfaction, a sense of duty, and continuous professional growth. Despite physical challenges and the need to balance various commitments, they demonstrate resilience and contribute significantly through knowledge transfer and mentorship. Moreover, aging reservists are crucial for military effectiveness, benefiting from and necessitating strong support systems for their continued service. It was recommended to establish health and wellness programs, mentorship initiatives, improved access to medical care, enhanced legislative policies, and recognition programs. Additionally, vocational training relevant to military and civilian roles and community-based integration programs are advised to maintain an effective reserve force and support national defense readiness.